Instability and corruption in student governance caused by tender system in universities - Sebake, B. K. (My University, 2016)
The landscape of Higher Education in South Africa has made a significant move to recognise the “voice of the voiceless” and embraced democracy at all cost. This argument is attested by the establishment of the Student Representative Councils (SRC’s) in all Universities to embrace inclusive governance through representation in statutory committees as determined by the Higher Education Act: 101 of 1997 as amended and the statutes of Universities respectively. The current analysis of the role of student leaders in the supply chain committees of Universities in South Africa has been contested as having a personal enrichment on individual student leaders themselves, and it can stifled progress in some parts of the Universities. This article examines tendencies of self-enrichment and how they impact on student governance. This article also calls for and examines ethical consideration in supply-chain and its relations to the experiences of the student leaders in Universities student governance. The sample is conducted on selected Universities of Technologies in three provinces inter alia: - Western Cape, Free State and Gauteng respectively. The article then include the overview of the role of student governance, the potential corrupt tendencies, and the theoretical analysis of the good governance, which is used to assess how Student Leadership embraces it. The study is then concluded and possible solutions to the current issues and problems will be identified in order to provide a scientific solution oriented study to improve the university governance.
Journal of Public Administration and Development Alternatives. Vol. 1, No.1, July 2016, 15-27
Keywords: Corruption; Good Governance; Accountability and responsibility; Democracy; Tender system - South Africa; Student participation in tender committees; Universities and colleges -- South Africa -- Business management; Universities and colleges -- South Africa -- Administration; Student participation in Administration -- South Africa